Use of a Catalytic Chiral Leaving Group for Asymmetric Substitutions at sp3‐Hybridized Carbon Atoms: Kinetic Resolution of β‐Amino Alcohols by p‐Methoxybenzylation. Issue 42 (6th October 2016) - Kuroda, Yusuke; Harada, Shingo; Oonishi, Akinori; Kiyama, Hiroki; Yamaoka, Yousuke; Yamada, Ken‐ichi; Takasu, Kiyosei
Abstract: A catalytic strategy was developed for asymmetric substitution reactions at sp 3 ‐hybridized carbon atoms by using a chiral alkylating agent generated in situ from trichloroacetimidate and a chiral phosphoric acid. The resulting chiral p ‐methoxybenzyl phosphate selectively reacts with β‐amino alcohols rather than those without a β‐NH functionality. The use of an electronically and sterically tuned chiral phosphoric acid enables the kinetic resolution of amino alcohols through p ‐methoxybenzylation with good enantioselectivity. Abstract : By your leave : A strategy for asymmetric substitutions based on the use of a catalytic chiral leaving group was demonstrated with a chiral phosphate generated in situ from trichloroacetimidate and a chiral phosphoric acid. An electronically and sterically tuned chiral phosphoric acid was developed to enable the kinetic resolution of amino alcohols through p ‐methoxybenzylation with good enantioselectivity.